Assessment of intestinal permeability of paclitaxel in the presence of NSAIDs and P-glycoprotein inhibitors - Zahra Sobhani; Hashem Montaseri; Soliman Mohammadi Samani; Fatemeh Ahmadi (Shiraz University of Medical Sciences, 2017)
Paclitaxel is a potent anticancer drug with a unique mechanism of action, which is now administered via IV infusion. Due to the presence of cremophor EL in its formulation it may show anaphylactic reactions. So that oral administration of paclitaxel for removal of these important side effects is the interest of many researches. Intestinal permeation of paclitaxel is restricted because of low solubility, lack of intestinal permeability, and efflux by pumps in intestinal wall. In this study the effects of NSAIDs and P-glycoprotein inhibitors on the intestinal permeability of paclitaxel was assessed by everted intestinal sacs technique. The results show that piroxicam, indomethacin, naproxen, mefenamic acid, and ibuprofen increase the intestinal permeability of paclitaxel 15.5, 10.1, 7.5, 5.6 , and 4.5 folds, respectively. Inhibition of the P-gp pumps by verapamil and cyclosporine increase the permeation of paclitaxel 2.9 and 4 folds, respectively. It seems that co-administration of paclitaxel with NSAIDs and P-gp pumps inhibitors could improve the intestinal permeation of paclitaxel.